(3CfHGA GdeDjO GdLdjd eQGO HHfGA HjJ GdhgGH GdLhGOs - (3GHf YdGf , eMeO Hf Ydj Hf eMeO YdGf Hf EHQGgje GdHcQj GdUOjbj,J (B1057 (3g` s
(3ChdgG (B:s
(3hHYO deG Je JGQjNj GdcHjQ ai bUI GdSjd GdPi SbW efg HjJ Gddg GdMQGe aCTGQ Ydi ef ETGQJg Zfe hHQ hcQGeI s
(3BNQgG (B:s
(3bGd eUfag YaGGddg Yfg(B: (3GfJgi edNUg VMhI GdfgGQ ef jhe GdSHJ GdSGHY hGdYTQjf ef Pi GdbYOI GdMQGe YGe (B1040 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B293s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B52 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs